2021
DOI: 10.3390/molecules26195995
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Compound Hydrophobic Usnic Acid and Hydrophilic Potassium Usnate Derivative: Applications and Comparisons

Abstract: Usnic acid is the best-studied lichen metabolite, presenting several biological activities, such as antibacterial, immunostimulating, antiviral, antifungal, anti-inflammatory, and antiparasitic agents; despite these relevant properties, it is a hydrophobic and toxic molecule. In this context, scientific research has driven the development of innovative alternatives, considering usnic acid as a source of raw material in obtaining new molecules, allowing structural modifications (syntheses) from it. The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Furthermore, increasing the UA concentration leads to lower zeta potential values ( Figure 5 a) measured in PBS, which is in accordance with previously published literature [ 23 ] and could be justified by the hydrophobicity of UA [ 24 ]. However, the MNP@5UA_CP sample shows a similar zeta potential value as the pristine sample, which is explained by the significantly reduced loading, i.e., 0.58%.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, increasing the UA concentration leads to lower zeta potential values ( Figure 5 a) measured in PBS, which is in accordance with previously published literature [ 23 ] and could be justified by the hydrophobicity of UA [ 24 ]. However, the MNP@5UA_CP sample shows a similar zeta potential value as the pristine sample, which is explained by the significantly reduced loading, i.e., 0.58%.…”
Section: Resultssupporting
confidence: 91%
“…In an attempt to study the possible mechanism of antiviral action, which was revealed for a number of compounds in experiments on live virus, we performed molecular modeling of the interaction of compounds with the active site of the main protease of SARS-CoV-2. Given the known reactivity of usnic acid [ 54 , 55 ], it was assumed that covalent binding of the SH-group of the catalytic amino acid residue Cys145 is unlikely. Therefore, non-covalent docking to the active site of the main protease was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the lack of available GA amount, we were not able to find lethal and semi-lethal concentrations of this compound, which seems to be a limitation of our study. Due to the absence of prior in vivo studies involving GA, we opted to utilize a similar dosage that has been employed for other secondary metabolites, such as atranorin [ 38 , 39 ], or usnic acid [ 40 ]. Accordingly, GA was administered orally at a concentration of 10 mg/kg body weight on a daily basis for a duration of one month, as outlined in the Materials and Methods section.…”
Section: Discussionmentioning
confidence: 99%